Nanoemulsion: A Promising Nanotechnology Tool to Achieve the Unmet Oral Bioavailability Enhancement Needs - Panwar, Jonee; Ekbbal, Rustam; Ali, Hasan (Drug Delivery Letters, 2025)
BackgroundLow oral permeability and low aqueous solubility are considered significant obstacles in achieving systemic therapeutic concentration to show optimum pharmacological response. Pharmaceutical scientists endeavored to overcome the above-stated problem after utilizing various approaches like salt formation, pro-drugs, co-solvency, complexation, solubilization, pH adjustment, sold dispersion, hydrotrophy, and nanotechnology-based techniques.ObjectivesAmong these approaches, nanotechnology-based drug carrier systems have been investigated to address the challenges of the drugs exhibiting poor oral absorption. Essentially, these systems have the potential to overcome the limitations associated with the oral route of drug administration. Among various nano-technological tools, nanoemulsion plays an important role in the bioavailability enhancement of biopharmaceutical classification system Class II, and Class IV drugs, in general and, Class III, in particular.MethodsA nanoemulsion is a colloidal system with a size in nanometers, an increased fraction of the dispersed phase, and intensified transparency. Either water is dispersed in oil (w/o type) or oil is dispersed in water (o/w type), and it has a longer shelf life.ResultsNanoemulsion is being utilized as an important drug carrier for bioavailability enhancement; however, it poses some challenges, such as clinical translation, large-scale manufacturing, and regulatory guidelines.ConclusionThe current review aims to compile and discuss the problems faced in the delivery of drugs exhibiting poor oral absorption, challenges faced in oral drug delivery, oral absorption enhancement techniques, mechanism of oral uptake using nanoemulsion, various modifications of nanoemulsion, clinical status, large-scale manufacturing, regulatory status, and new prospects in the future.
Keywords: Pharmaceutical nanotechnology